(untitled) (REMUNOM, 2025)
The current work examines the conceptual investigation concerning the assessment of collective judicial jurisdiction in the procedural legal system of the environment, with the primary aim of expounding the crucial aspects regarding certain subjects linked to environmental law, such as, for example, procedural elements, the environmental public civil action, the environmental popular action, the environmental collective writ of mandamus, and the environmental writ of injunction. Thus, a theoretical examination was carried out, through bibliographic and documentary research in sources of a legal nature, integrating laws, jurists’ teachings, and judicial decisions. Initially, a brief explanation of the chronological progression of environmental law is presented. Subsequently, the main legal aspects of the aforementioned topics are discussed. Through this analysis, the relevance of environmental law in the nation is observed and can be deemed adequate to ensure the conditions for the conservation of the ecosystem; however, legal tools are indispensable to ensure its applicability.